The Disposal of Mine Tailings Material - Hoare, Bert (University of Waterloo, 2014)
The mining industry is an important component of the Canadian economy. The principal waste material from this industry is tailings. Numerous failures of tailings dams have caused loss of life and serious pollution problems. This thesis relates to the broad scale investigation and development of improved methods for tailings disposal. A systematic morphology has been developed which provides an effective approach to the overall problem for long-term planning and design. Improved design and construction techniques are advanced for the hydraulic construction of tailings dams with mobile hydrocyclones. The new design incorporates a sealed structure to improve the structural quality and safety of the dam by reducing and maintaining the porewater pressure at zero or negative values over the long-term period. Significant economic benefits are also attainable with the new design techniques. Economic advantages and structural considerations are presented for the system to decant effluent from the tailings basin. Special instrumentation has been designed, developed, and tested which will facilitate the evaluation of the material shear strength for this specific type of tailings dam.
Keywords: mine tailings; Civil Engineering